Resting Heart Rate Variability, Perceived Emotion Regulation, and Low-Risk Drug Use in College-Aged Adults: Gender as a Moderator - Kwon, Enoch S.; Kittaneh, Ahmad A.; Gerardo, Gina M.; Koenig, Julian; Thayer, Julian F.; Williams, DeWayne P. (Frontiers in Psychiatry, 2022)
Identification of individual differences in drug use is warranted, as a history of use is associated with future drug problems. Such drug use is thought to disrupt inhibitory and motivation networks involved in emotion regulation (ER). Higher resting heart rate variability (HRV), a biomarker of effective inhibitory abilities, is associated with less substance (e.g., alcohol, opioid) use. Higher HRV is associated with lower perceived ER difficulties, and this link is stronger in women relative to men. Evidence suggests women might engage in drug use primarily to reduce stress, and men primarily to induce feelings of elation. Research has yet to examine associations among individuals’ difficulties in ER, resting HRV, and a recent history of drug use; the current study explored this, in addition to how these associations might differ as a function of gender. Young and healthy college students (N = 190; 88 women) completed a 5-min baseline to assess resting HRV, followed by the 36-item Difficulties in ER Scale and 10-item Drug Abuse Screening Test. Higher difficulties in ER, but not resting HRV, were associated with a greater history of “low-risk” drug use in the full sample and moderation tests confirm this link was stronger in women. Moderated-mediation results confirmed an indirect association between resting HRV and drug use, mediated by self-reported difficulties among women only. A significant association between resting HRV and DERS emerged only among women without a history of drug use. These results indicate that difficulties in ER are both associated with a low-risk history of drug use and underlie an indirect link between resting HRV and drug use history in women only. Among these women with a history of drug use relative to women without, there was no link between resting HRV and self-reported difficulties in ER, suggesting a disrupted inhibitory-motivational pathway. Additional work is needed to understand the psychophysiological correlates of a history of low-risk drug use in young men. These data are in line with research suggesting gender differences in the motivation to engage in recreational drug use and ER interventions might be important in women who engage in low-risk recreational drug use.